The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/3510216/2020
|View full text |Cite
|
Sign up to set email alerts
|

“CORRO COM O PCC”, “CORRO COM O CV”, “SOU DO CRIME” Facções, sistema socioeducativo e os governos do ilícito em Alagoas

Abstract: Neste texto, discuto as transformações recentes no sistema socioeducativo e suas relações com as balanças de poder entre jovens e adolescentes com alianças faccionais, além de outros atores de mercados ilícitos em Alagoas. Retomo o problema da regulação/desregulação dos conflitos nas “periferias” em um contexto no qual a expansão do dinheiro e de redes criminais se entrelaçam à expansão da urbanização em pequenas e médias cidades do Norte-Nordeste. A partir de registros de campo em unidades de internação e ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
0
9
0
8
Order By: Relevance
“…The debate regarding homicides in Brazil has brought important new considerations to the literature. It has already been found that in practically all contexts where there has been a significant rise in homicide rates (such as Rio de Janeiro in the 1980s, São Paulo in the 1990s and the states of the Northeast in the last decade) there were highly profitable illegal markets being established and disputed by armed groups (MANSO and GODOY, 2014;RATTON and DAUDELIN, 2018;MANSO and DIAS, 2018;FELTRAN, 2018FELTRAN, , 2019KAHN, 2021;RODRIGUES, 2019aRODRIGUES, , 2020a.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The debate regarding homicides in Brazil has brought important new considerations to the literature. It has already been found that in practically all contexts where there has been a significant rise in homicide rates (such as Rio de Janeiro in the 1980s, São Paulo in the 1990s and the states of the Northeast in the last decade) there were highly profitable illegal markets being established and disputed by armed groups (MANSO and GODOY, 2014;RATTON and DAUDELIN, 2018;MANSO and DIAS, 2018;FELTRAN, 2018FELTRAN, , 2019KAHN, 2021;RODRIGUES, 2019aRODRIGUES, , 2020a.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was the CV that, in 2005, introduced crack into the local market and engaged in more and more disputes for drug-dealing spots, including the involvement of low-ranking police officers (RODRIGUES, 2017b(RODRIGUES, , 2019a(RODRIGUES, , 2020a(RODRIGUES, , 2021a(RODRIGUES, , 2021bCARVALHO, 2021).…”
Section: Rising Rates: a Detailed Explanationmentioning
confidence: 99%
“…A expansão de grupos faccionados por prisões alagoanas, bem como por periferias da capital e de cidades interioranas, seguiu-se a esse processo. Desde essa época a presença do PCC vinha sendo identificada de modo marginal em cadeias de Alagoas, mas foi o CV que, em 2005, inseriu o crack no mercado local e se engajou em cada vez mais disputas por pontos de venda de drogas, inclusive com participação de policiais de baixa patente (RODRIGUES, 2017b(RODRIGUES, , 2019a(RODRIGUES, , 2020a(RODRIGUES, , 2021a(RODRIGUES, , 2021bCARVALHO, 2021). Entre 2005 e 2011 ocorreu uma transição nas formas de governo sobre os mercados ilegais em Maceió.…”
Section: Taxas Em Elevação: Detalhamento Da Explicaçãounclassified
“…Almost half (48.6%) of all people imprisoned in 2020 were aged 18 to 29. The issue becomes more complex if we consider the expansion of the "world of crime" (FELTRAN, 2020) since the 1990s, which has been characterized by the emergence of criminal gangs that act collectively to produce territorial, ethical-normative and market "governance" (LESSING, 2020;FELTRAN, 2018FELTRAN, , 2020MANSO and DIAS, 2018;RODRIGUES, 2020aRODRIGUES, , 2020bBIONDI, 2014). The forms of such governance depend on the groups to be regulated, their configurations and context (LESSING, 2008(LESSING, , 2020FELTRAN, 2011).…”
Section: Interregional Comparisonsmentioning
confidence: 99%